A novel resolver-to-DC converter based on OTA-based inverse-sine function circuit - Kaewpoonsuk, Anucha; Petchmaneelumka, Wandee; Rerkratn, Apinai; Tammaruckwattana, Sirichai; Riewruja, Vanchai (My University, 2008)
A new technique for realizing the resolver-to-DC converter using the OTA-based inverse-sine function circuit is presented. The proposed converter comprises the demodulator, absolute detector, minimum detector, ± unity-gain amplifier, controlled signal logic circuit, and OTA-based inverse-sine function circuit. The output voltage is linearly proportional to the resolver angle with maximum absolute error of about 0.195%, which is less than the error from the conventional resolver-to-DC converter based on the similar OTA-based inverse-sine function circuit. PSPICE simulation and experimental results verifying the performances of the proposed circuit are in close agreement with the expected values. © 2008 SICE.
Keywords: Inverse-sine function circuit; OTA; Resolver converter; Resolver-to-DC; Sine-to-triangular wave converter